Thermal performance with depth: Comparison of a mesophotic scleractinian and an antipatharian species subjected to internal waves in Mo'orea, French Polynesia. (February 2023) - Godefroid, Mathilde; Dubois, Philippe; Hédouin, Laetitia
Abstract: Local thermal environment has a strong influence on the physiology of marine ectotherms. This is particularly relevant for tropical organisms living close to their thermal optimum, well exemplified by the increasing frequency of bleaching occurrence in shallow-water corals. Mesophotic Coral Ecosystems (MCEs) were suggested as potential oases, especially when they are submitted to internal waves inducing short-term cooling events. Indeed, probability of bleaching occurrence in scleractinians was reported to decrease with depth in Mo'orea as temperature variability increases. However, ecophysiological data are currently lacking to understand the cause of lower susceptibility/increased plasticity of deeper corals. A growing interest has been devoted the last decade to MCEs, but our understanding of the physiological performance of benthic organisms living in this environment remains relatively unexplored. To tackle that question, we first compared the metabolic responses (dark respiration, net photosynthesis and photosynthetic efficiency) of the depth-generalist scleractinian Pachyseris speciosa from two heterogeneous thermal environment (25 and 85 m depths) to acute heat stress to determine if the local thermal environment could predict coral response to warming. Then, we tested the thermal performance of two sympatric species (the scleractinian P. speciosa and the antipatharian Stichopathes sp.) to determine if there are inter-species differences in performances in species experiencing identical levels of temperature variability, at mesophotic depths (85 m). Results revealed broader thermal performances in the mesophotic P. speciosa compared to mid-depth ones, and constrained performances in the mesophotic antipatharian compared to the scleractinian species. We hypothesize that the high fluctuations in temperature due to internal waves in deeper areas contribute to the broader thermal performances of mesophotic P. speciosa. However, the constrained performances of the mesophotic antipatharian compared to P. speciosa suggests that other processes than the symbiosis with zooxanthellae also influence thermal performances of these mesophotic organisms. Our results supported that Stichopathes sp. lives close to its thermal optimum, suggesting a (relatively) cold thermal specialist strategy. In this context, composition of MCEs in the future is unlikely to shift to antipatharian-dominated landscape and will remain coral-dominated landscape. Graphical abstract: Image 1 Highlights: P. speciosa has broader thermal performance at 85 than 25 m. Thermal regime likely explains depth-specific thermal performance for P. speciosa . At 85 m depth, thermal performance is narrower for Stichopathes sp. than for P. speciosa . Cooling events generated by internal waves do not always improve thermotolerance. Stichopathes sp. at 85 m lives close to its thermal optimum.